UV Pretreatment Impairs the Enzymatic Degradation of Polyethylene Terephthalate - Falkenstein, Patricia; Gräsing, Daniel; Bielytskyi, Pavlo; Zimmermann, Wolfgang; Matysik, Jörg; Wei, Ren; Song, Chen (Frontiers in Microbiology, 2020)
The biocatalytic degradation of polyethylene terephthalate (PET) emerged recently as a promising alternative plastic recycling method. However, limited activity of previously known enzymes against post-consumer PET materials still prevents the application on an industrial scale. In this study, the influence of ultraviolet (UV) irradiation as a potential pretreatment method for the enzymatic degradation of PET was investigated. Attenuated total reflection Fourier transform infrared (ATR-FTIR) and 1H solution nuclear magnetic resonance (NMR) analysis indicated a shortening of the polymer chains of UV-treated PET due to intra-chain scissions. The degradation of UV-treated PET films by a polyester hydrolase resulted in significantly lower weight losses compared to the untreated sample. We also examined site-specific and segmental chain dynamics over a time scale of sub-microseconds to seconds using centerband-only detection of exchange (CODEX), rotating-frame spin-lattice relaxation (T1ρ), and dipolar chemical shift correlation (DIPSHIFT) experiments which revealed an overall increase in the chain rigidity of the UV-treated sample. The observed dynamic changes are most likely associated with the increased crystallinity of the surface, where the consequence is a decreased accessibility for the enzyme-catalyzed hydrolysis. Moreover, our NMR study provided further knowledge on how polymer chain conformation and dynamics of PET can mechanistically influence the enzymatic degradation.